The effects of bretylium on the subcellular distribution of noradrenaline and on adrenergic nerve function in rat heart - Abbs, E. T. (1973)
1. The effects of bretylium were investigated on the content and subcellular distribution of noradrenaline in the rat heart and on the response to stimulation of the sympathetic nerves supplying the heart. 2. In most experiments bretylium produced no change in the total noradrenaline content of the heart but significant changes were produced in the subcellular distribution of noradrenaline. 3. Treatment with amphetamine both prevented and antagonized the bretylium-induced adrenergic neurone blockade and most of the accompanying changes in the subcellular distribution of noradrenaline. 4. There was a temporal correlation between the bretylium-induced depletion of noradrenaline from the microsomal (P(2)) fraction and adrenergic neurone blockade. 5. The onset of adrenergic neurone blockade was also accompanied by an elevation of the noradrenaline content in the low-speed coarse (P(1A)) fraction and in the mitochondrial (P(1B)) fraction; this elevation was prevented by pretreatment with α-methyl-p-tyrosine. 6. It is concluded that although the elevation of the noradrenaline content of the P(1A) and P(1B) fractions and a depletion of amine from the P(2) fraction are associated with the onset of adrenergic neurone blockade only the depletion from the P(2) fraction is required for its maintenance. This conclusion supports the hypothesis that only a small portion of the noradrenaline content of an adrenergically-innervated organ is associated with the release of transmitter, for when this small `store' is depleted, by agents like bretylium, the nerves fail to function.